Workshop On The Implementation Of Balanced Nutrition Messages To Prevent Anemia In Female Adolescent: Workshop Penerapan Pesan Gizi Seimbang Untuk Mencegah Anemia Remaja Putri - Wery Aslinda; Elvyrah Faisal; Asriani; Bahja (Poltekkes Kemenkes Palu, 2022)
Adolescents are the nation's assets for the creation of a better future generation. Adolescence is a time of rapid changes in terms of physical, cognitive, psychosocial or behavioral growth. Female adolescent often experience problems, one of which is anemia. Anemia is a deficiency (deficiency) of red blood cells due to low hemoglobin levels in the body. Anemia that occurs in female adolescent can interfere with the process of growth and development. The purpose of this community service is to increase the knowledge and awareness of female adolescent regarding balanced nutrition messages and anemia. The method used is public education by utilizing the media (food model). The results of this activity showed that 30.5% of female adolescent had anemia, 41,7% of female adolescent with good knowledge, and increased to 93,3% after training. The conclusion of this community service activity is that there is an increase in knowledge and awareness of female adolescent related to anemia by implementing a balanced nutrition messages. Through this activity, participants are expected to maintain a healthy lifestyle with balanced nutrition guidelines and make efforts to prevent anemia.